Four thousand weeks time management for mortals - Burkeman, Oliver (New York Straus and Giroux, 2021)
A lively philosophical guide to time and time management, setting aside superficial efficiency solutions in favor of reckoning with and finding joy in the finitude of human life
Includes index.
Keywords: Time management